Kebijakan Pengembangan Pariwisata Tangguh Bencana Melalui Kolaborasi dan Manajemen Pariwisata Kebencanaan Terintegrasi - Berliandaldo, Mahardhika; Prasetyo, Ari; Sakti, Viky Pemuda Indra (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
The development of disaster-resilient and disaster-safe tourism policies, policy strengthening and implementation of collaboration will be integrated into one disaster tourism management framework. In the past decade, Indonesia has never been separated from the threat of disasters or crises that hurt Indonesia's economic growth. Tourism suffers considerable losses from a tragedy or crisis that befell our country. Through the development of resilient and disaster-safe tourism, policy strengthening and collaboration implementation will integrate into one disaster tourism management framework aimed at strengthening the tourism sector's resilience and contributing to social and economic aspects. This article uses desk study and descriptive-analytical approaches. The author finds that the development of disaster-resilient tourism must be synergized with the context of disaster management, namely the pre-disaster stage, when a disaster occurs, and the post-disaster step, which is implemented through an alignment scheme for tourism policy and disaster management as well as collaboration between stakeholders through five stages of the program which aims to provide quick and responsive resolution and collaboration steps in dealing with recovery and long-term resilience actions, especially in the tourism sector with an integrated disaster tourism management framework. Some of the recommendations from this study include the New Regulation, which explicitly regulates disaster-resilient tourism, the intensive collaboration between ministries/institutions, the synergy of tourism programs and disaster management for disaster-prone destinations, and the realization of integration of tourism and disaster policies.